Advancing subsurface characterization through borehole optical imaging: A comprehensive review - Ding-Jian Wang; Yunfeng Ge; Tao Wen; Zhiqiang Fan; Yahui Zhang (Tunnelling and Underground Space Technology, 2026)

Dual-phage formulation (STP55/LSA2308)-loaded gelatin hydrogel films for simultaneous pathogen control: physicochemical characterization and antibacterial efficacy in food matrices - Yifeng Ding; Peng Guan; Ge Zhou; Chenxi Huang; Yujie Huang; Jia Wang; Yanchun Shao; Xiaohong Wang (Food Hydrocolloids, 2026)

Soil salinity inversion and spatiotemporal dynamics in cotton fields in the Wei–Ku oasis - Jinming Zhang; Jianli Ding; Jinjie Wang; Zihan Zhang; Liya Shi; Xiangyu Ge (CATENA, 2026)

Spatiotemporal storm surge forecasting with a deep learning model using an augmented typhoon track dataset and meteorological updates - Zaiyang Zhou; Zejun Wu; D.S. van Maren; Xinyi Shen; Jun Ding; Jianzhong Ge (Coastal Engineering, 2026)

Skin bacteriota ameliorates androgenetic alopecia via harmonizing skin immuno inflammatory balance - Yichen Cao; Xusheng Wu; Zixuan Huang; Chen Xu; Zengyan Ge; Yixin Xie; Lan Wu; Ying Qian; Bin Ding; Hongbin Luo (Brazilian Journal of Microbiology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Gelatin-based hydrogel films incorporating bacteriophages: A novel strategy for controlling Salmonella contamination in foods - Yifeng Ding; Ge Zhou; Peng Guan; Ting Zhang; Yulin Wang; Jia Wang; Yanchun Shao; Xiaohong Wang (Food Control, 2026)

Preparation of coal gasification coarse slag-based low-carbon cementitious materials based on supersulfated cement system: matching mechanism between reaction path induced by multi-mineral salts and mechanical properties - Xiaowei Ge; Xiaowei Gu; Ziyang Hu; Shenyu Wang; Xu Wang; Shaoqian Liu; Xuecheng Ding; Jinchi Han; Jianping Liu; Hao Wang; Xuemei Liu (Chemical Engineering Journal, 2026)

Structure-activity relationship of per- and Polyfluoroalkyl substances as inhibitors of human and rat 17β-Hydroxysteroid dehydrogenase 3 - Chengshuang Pan; Jingjing Li; Fuhong Tian; Chentao Ding; Shaowei Wang; Ren-shan Ge; Qianjin Fei; Yang Zhu (Toxicology and Applied Pharmacology, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Bottom-up construction of betaine-grafted iCOF: Selective adsorption of Cr(VI) via precise host-guest interaction - Zhihui Wen; Erli Ding; Yongjie Bai; Xiaochan Liu; Yourong Wei; Ge Li; Benhua Xu; Bingxin Liu (Chemical Engineering Journal, 2026)

Photo-stimulated reductive dissolved Fe2+ from epitaxial twinned goethite accelerated by fulvic acid: Insight from the band structure and photochemical activity - Shanshan Yang; Fei Liu; Xiao Ge; Hongrui Ding; Anhuai Lu (Applied Geochemistry, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

PTPRO Governs Synaptic Density, Long-Term Potentiation and Cognitive Function In Vivo - Xiangdong Wang; Jiaguo Wu; Mengna Liu; Kun Zhang; Xinping Yuan; Fangting Xing; Wenjie Xu; Yulin Zheng; Yifei Wu; Lin Luo; Xinyi Ding; Ge Gao; et al. (Neuroscience Bulletin, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Relative Localization of a Floating Recovery Target in an Unmanned Surface Platform-Assisted UAV–ROV Search-and-Recovery System Under High Sea States - Hongkun Zhou; Yunfei Ding; Hanlin Gao; Gang Wang; Tong Ge; Ying Zhang (Journal of Marine Science and Engineering, 2026)
This study addresses target-to-ROV relative localization in an unmanned surface platform-assisted UAV–ROV search-and-recovery system. Because the submerged ROV is not assumed to be visible from the air, the UAV observes the floating target and a GNSS-equipped ROV-associated surface buoy in the same image. The buoy position and target-to-buoy image displacement are combined to construct a world-frame target-position measurement, whose covariance accounts for buoy GNSS uncertainty and correlated image-projection errors. An upward-looking ROV imaging sonar provides range–bearing measurements. A delay-aware extended Kalman filter fuses the asynchronous observations using sea-state- and confidence-dependent covariance adaptation and normalized-innovation gating. ROV acoustic/inertial navigation uncertainty is propagated into the sonar measurement covariance and the reported relative-state covariance, avoiding duplication of the same navigation error in the aerial channel. The method is evaluated using a JONSWAP-based temporal disturbance model, Monte Carlo simulations, and single-factor and joint sea-state–occlusion–delay sensitivity tests. Under the nominal sea-state-5 condition, the proposed method achieves a mean ROV-frame relative RMSE of 0.992 m, compared with 1.083 m for ROV-only localization and 1.054 m for fixed-covariance fusion, with no run exceeding the 5 m divergence threshold. The results demonstrate improved relative-localization robustness within the simulated environment.

Retraction notice to “Physicochemically protected organic carbon release is the rate-limiting step of rhizosphere priming in paddy soils” [Sci. Total Environ. 955 (2024) 176859] - Cuiyan Wu; Wei Huang; Yixian Liu; Han Li; Shuai Ding; Zhenke Zhu; Feng Wang; Feike A. Dijkstra; Guangbin Zhang; Yakov Kuzyakov; Weiguo Cheng; Mouliang Xiao; et al. (Science of The Total Environment, 2026)

Experimental and Numerical Investigation of Various Thermal Barrier Materials for Mitigating Thermal Runaway Propagation in Lithium-Ion Battery Modules - Hongbo Ge; Yin Yu; Hongjing Zi; Bolin Hu; Kangjie Ding; Chengdong Wang; Shaoyang Zheng; Yezhi Xia; Pengjie Liu; Qingsong Wang (Process Safety and Environmental Protection, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

PM2.5-attributable chronic disease burden in BRICS–plus countries, 1990–2021: temporal trends and health benefits from optimal control - Jiachang Wei; Mengfei Yang; Yiyang Sun; Quanxi Ge; Sha Yang; Guanran Wang; Jing Ding; Sihan Sun; Li Li (Air Quality, Atmosphere & Health, 2026)

A Portable Smartphone-assisted Sensor for Detection of Iodate Based on Triphenylamine Oligomer - Yue Zhang; Mingyi Guan; Hui Li; Xiaoyu Zeng; Lu Yang; Xiaofang Ding; Xiaoping Fan; Daoxing Chen; Mengtuan Ge (Journal of Fluorescence, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Polygonatum polysaccharide boosts nanozyme behavior of anthocyanin-derived carbon dots for alleviating alcohol-associated liver injury - Chenchen Dai; Weixia Qin; Zifei Ge; Hao Cai; Haimei Zhu; Haizhen Ding; Hong Bi (Food Bioscience, 2026)

Removal of trace 17α-ethinylestradiol by microalgal-bacterial granular sludge: The overlooked role of extracellular photosensitization - Hongpu Xue; Xiangwei Ding; Wei Zhang; Li Ge; Yi Bao; Qingmiao Yu; Yujie He; Jinju Geng (Environmental Research, 2026)

From selection to design: Reshaping aptamer discovery with artificial intelligence - Xin Yang; Shijian Ding; Meishen Ren; Huarui Zhang; Xiaohui Tao; Ning Zhang; Yihao Zhang; Hewen Jiange; Yufei Pan; Shanshan Yao; Luyao Wang; Yuan Ma; et al. (Chemical Engineering Journal, 2026)

Ketjen black conductive network enabled proton-blocking and dendrite-free zinc metal anodes - Xilian Xu; Jinshuai Zheng; Liang Liang; Rongkuan Ding; Gao Cheng; Chenlei Tao; Shengli Lu; Ying Wu; Ge Feng (Chemical Engineering Journal, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

An MPC-ECMS Integrated Energy Management Strategy for Shipboard Gas Turbine–Photovoltaic–Hybrid Energy Storage Power Systems - Zhicheng Ye; Zemin Ding; Jinzhou Fu; Ge Xia (Journal of Marine Science and Engineering, 2026)
A real-time optimized model predictive control–equivalent consumption minimization strategy (MPC-ECMS) is proposed for the energy management of shipboard gas turbine–photovoltaic hybrid energy storage (GT-PV-HESS) power systems. Different from conventional MPC-ECMS methods that only adopt single-level SOC-based feedback regulation, the strategy aims to overcome the limitations of conventional methods, including the poor adaptability of rule-based strategies and the lack of foresight in traditional ECMS, which cannot achieve simultaneous improvements in fuel economy, generation efficiency, and battery lifespan while maintaining system stability under dynamic operating conditions. The proposed strategy integrates the forward-looking optimization ability of MPC and the real-time decision-making advantage of ECMS. MPC is used to predict short-term load and photovoltaic power and identify operating modes, and a two-level equivalent factor adjustment mechanism is designed based on predicted conditions and battery state of charge (SOC). The optimized factor is applied in ECMS to achieve optimal power allocation between the gas turbine and battery under system constraints, while the supercapacitor implements power secondary correction to suppress bus voltage fluctuations caused by gas turbine operation. The architectural novelty lies in the two-level coordination mechanism and the marine-oriented hybrid energy storage cooperation. Simulation studies are conducted on the MATLAB/Simulink R2021b platform, and the results validate that it yields superior performance to the rule-based control and traditional ECMS under typical ship operating conditions. It increases gas turbine efficiency to 15.62% (0.47% and 6.24% higher than the two conventional methods). Over the 120 s simulation period, the proposed strategy reduces total fuel consumption to 1.049 kg, which is lower than 1.054 kg for the rule-based strategy and 1.192 kg for conventional ECMS. The battery SOC fluctuation is restricted to only 3.89%. The maximum DC bus voltage fluctuation rate is controlled within 3.28%, which meets the stability requirements of shipboard DC microgrids. The proposed strategy achieves a comprehensive and superior balance among fuel economy, power generation efficiency, and battery life while ensuring stable system operation under all working conditions. This two-level MPC-ECMS framework provides a high-performance and practically feasible energy management solution for shipboard hybrid power systems.

Hydrophobic high-frequency vibration collaborative strategy for reducing resistance and soil adhesion of tillage tools in lime concretion black soil - Kuan Qin; Ding Zhang; Biao Ma; Weidong Gao; Chengmao Cao; Xu Zhu; Junjie Lu; Wei Wang; Jun Ge; Qichun Feng; Huaizhi Liu; Siliang Liu; et al. (Soil and Tillage Research, 2026)

Safe path planning and fault-tolerant formation control of NMSVs under cyber and actuator failures - Zhi-Kui Wang; Teng-Fei Ding; Ming-Feng Ge; Chang-Duo Liang (Ocean Engineering, 2026)

A framework approach for analyzing water transformation characteristics of typical watersheds in arid zones during irrigation periods - Jingming Liu; Jianli Ding; Jinjie Wang; Zhe Zhang; Jie Zou; Zipeng Zhang; Xiao Wang; Zan Fu; Xiangyu Ge (Environmental Modelling & Software, 2026)

Tracing molybdenum mineralization through hydrothermal biotite geochemistry in the Jinduicheng porphyry deposit, East Qinling, China - Zhenyu Qin; Fan Yang; Xiaoyu Ge; Leon Bagas; Zhaoyue Ding; Luyang Wang; Lifeng Xu (Journal of Geochemical Exploration, 2026)

Long-chain alkyl-modified quaternized laminarin for enhanced antibacterial activity and food preservation - Xing-Wei Li; Zhong-Fei Gao; Kai-Jie Dong; Yu-Lun Li; Gui-Ge Hou; Yue-Xia Ding; Yun Hou (Food Chemistry, 2026)

Dityrosine induces myocardial injury via Ang II-MAPK-Nrf2 pathway-mediated oxidative stress, mitochondrial dysfunction, and fibrosis in mice - Yin-Yi Ding; Jia Chen; Yuxin Wang; Zhenyu Gu; Tianyuan Song; Yujun Ge; Tianming Xuan; Oushan Tang; Qing Shen; Keyun Cheng (Food and Chemical Toxicology, 2026)

MTA-SM: Multi-machine path planning and time-window scheduling joint optimization method in hilly safflower harvesting - Liwei Yang; Ping Li; Zhongshuo Ding; Chao Sun; Fei Chen; Yijiang Zheng; Yun Ge (Computers and Electronics in Agriculture, 2026)

Effects of chronic ammonia nitrogen stress on intestinal barrier function and microbial composition of Chinese soft-shelled turtle (Pelodiscus sinensis) - Yujie Ding; Fa Dai; Lujia Su; Qiuya Huang; Feinan Shen; Guoying Qian; Chutian Ge; Jiehao Xu (Aquaculture, 2026)

Tributyl phosphate disrupts hepatic lipid metabolism via cGAS-STING signal pathway mediated inflammation - Liwei Yang; Zhili Ge; Xuehan Ding; Jingjing Shi; Jiaxin Zhang; Tianyou Wang; Huibin Jiang; Xinyu Zhang; Liting Zhou (Toxicology Letters, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Study on the mechanism of 3D printing HIPE gels stabilized by soybean protein isolate/bacterial cellulose co-assemblies through simulating the animal adipose tissue structure - Chong Wang; Jiaxin Zhao; Jiaoqiong Liu; Xincheng Ge; Yan Sunhui; Guanghong Zhou; Chao Ding; Xinbo Zhuang (Food Hydrocolloids, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Recombinant Escherichia coli displaying conserved dominant B-cell epitopes of porcine epidemic diarrhea virus (PEDV) spike protein confers protective immunity against PEDV - Shengmei Pang; Congrui Zhu; PHYU HNIN WAI; Ge Li; Peng Dai; Guowei Ding; Guoqiang Zhu; Meng Ge; Weiping Zhang; Qiangde Duan (Chemical Engineering Journal, 2026)

Electroreduction of nitrate to hydroxylamine over regenerable facet dependent bismuth nanosheet catalyst - Liwen Wang; Bingqing Ge; Xiaoxia Hou; Ningze Gao; Chenjia Liang; Xianghao Wang; Yan Zhu; Weiping Ding (Chemical Engineering Journal, 2026)

Understanding and experimental analysis of soil disturbance by tillage tools with different outer contours - Kuan Qin; Wei Wang; Chunsong Guan; Weidong Gao; Ding Zhang; Chengmao Cao; Junjie Lu; Xu Zhu; Jun Ge (Soil and Tillage Research, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Lightweight and high-strength foam concrete based on low-grade magnesite: Proportion optimization and performance characterization - Xiaowei Gu; Xuecheng Ding; Xiaowei Ge; Shenyu Wang; Hao Wang; Jianping Liu (Minerals Engineering, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

The law of oxidation and exothermic of low-rank coal at critical temperature: Based on the isothermal stage experiment method - Bing Lu; Xun Zhang; Ling Qiao; Cong Ding; Nan Fan; Ge Huang; Fengwei Dai (Fuel, 2026)

Edge-engineered graphite modulates SEI formation and enables fast-charging lithium-ion batteries - Xuanding Wang; Bingqing Hu; Xiaoting Cao; Shifei Huang; Jiang Xu; Shanhai Ge; Jianning Ding (Chemical Engineering Journal, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

CMSS1 promoted CXCL8-CXCR1/2 pathway to accelerate the invasion and immune escape of triple-negative breast cancer - Dequan Ding; Min Li; Xue Guo; Ge Wu; Yan Zhang (Journal of Molecular Histology, 2026)

Modulation of residual current and water flux by the construction of Yangshan deep-water harbour, Shanghai, China - Wei Mao; Wenyun Guo; Jianzhong Ge; Pingxing Ding (Regional Studies in Marine Science, 2026)

An improved spatiotemporal graph neural network framework for water quality assessment - Fei Ding; Haobin Yuan; Mingcen Jiang; Ziyue Luo; Miao Ge; Shilong Hao; Yang Hu; Hanjie Mao; Xin Xie; Wenpan Li; Yong Zhang (Journal of Water Process Engineering, 2026)

Intelligent food preservation systems based on MOFs-AI integration: technological breakthroughs and developmental trends - Xin Ding; Nasi Ai; Yiming Zhao; Lingyun Li; Ge Chen; Donghui Xu; Xiaomin Xu; Lin Qin; Jing Chen; Guangyang Liu (Food Chemistry, 2026)

Precision screening of Lactobacillus with potential anti-allergenic using dual cell model - Xiang-Ge Xin; Yue Meng; Zai-Chen Li; Jun Xi; Jun Meng; Chang-He Ding; Dong-Ge Zheng; Ling-Guang Du; Shu-Song Wang (Food Bioscience, 2026)

Fractional derivative viscoelastic models based on L2-1σ formula: modelling and numerical application - Pan Ding; Riqing Xu; Lixing Wang; Zhiran Gao; Xiaonan Ge; Minjie Wen (Computers and Geotechnics, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Nitrogen transformation and N2O production pathways under arsenic and cadmium stress in Chongming Island, China - Yinghui Jiang; Guoyu Yin; Minghua Nie; Caixia Yan; Mingjun Ding; Hua Zhang; Mei Lei; Yong Ge (Marine Pollution Bulletin, 2025)

Predicting the isotopic composition of precipitation in China via interpretable machine learning techniques - Jingming Liu; Jianli Ding; Jinjie Wang; Jie Zou; Zipeng Zhang; Qingling Bao; Xiao Wang; Xiangyu Ge (Journal of Hydrology, 2025)

Porous amorphous manganese oxide micro-nanostructures boosted electron transfer between periodate and organic contaminants: The significance of surface reactive oxygen species - Shuyang Deng; Rongyi Ge; Fan Yang; Xiao Guo; Hongrui Xiao; Kangle Lv; Yaobin Ding (Journal of Environmental Chemical Engineering, 2025)

High-performance antifouling electrochemical aptsensor based on a Y-shaped glycopeptide and platinum nanoparticles for detecting aflatoxin B1 in food - Cheng Zhang; Xujun Pu; Xian Chen; Jinzhi Liang; Kun Ge; Yangyue Ding; Lunzhao Yi; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Revisiting periodate photoactivation by solar light: Organic contaminant-specific and wavelength-dependent mechanism - Yiping Dong; Rongyi Ge; Hongrui Xiao; Fan Yang; Kangle Lv; Yaobin Ding (Chemical Engineering Journal, 2025)

Selective copper immobilization in contaminated soils using cysteine-modified chitosan: Mechanisms and efficacy - Feili Li; Ge Yu; Yuhan Li; Jiahao Wu; Tianzheng Ding; Wanting Qiu; Jingjing Fang; Zanfang Jin (Chemical Engineering Journal, 2025)

The possibility of Escherichia coli transmission from pregnant women to the neonates - Dongmiao Zhang; Xiaoling Ge; Yajuan Wang; Wei Gao; Yijun Ding; Jinjing Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The fungicide jinggangmycin stimulates fecundity of Nilaparvata lugens Stål via ILP/Foxo signaling - Xudong Zhao; Yuting Ding; Zhirou Duan; Di Deng; Zhiyue Mao; Yan Zhu; Xiaoxi Fan; Guohui Yu; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Predefined-time distributed optimal formation control of networked marine surface vehicles based on a nonsingular segmented terminal sliding mode method - Chang-Duo Liang; Yang Zhang; Qian Chen; Teng-Fei Ding; Ming-Feng Ge (Ocean Engineering, 2025)

Enhanced insecticidal activity and bioavailability of thiacloprid from pH-responsive porous MPN(Fe)@ZIF-8 nanocarrier - Miao Wang; Donghui Xu; Ying Zhang; Jie Zhou; Zhihao Lin; Yiming Zhao; Xin Ding; Bin Sheng; Xiaobin Wen; Xiao Song; Ge Chen; Xiaomin Xu; et al. (Journal of Cleaner Production, 2025)

Association of ambient fine particulate matter (PM2.5) and its constituents with risk of pulmonary nodules in a lung cancer screening project - Xinyuan Ge; Ci Song; Chen Zhu; Yang Ding; Maojie Liu; Juan Yang; Chan Tian; Jiahao Zhang; Lili Wu; Lingying Zhu; Lei Shi; Xiangdong Cheng; et al. (Environmental Research, 2025)

Isothiazolinone biocides as aromatase inhibitors: Hormonal disruption, and in silico docking and SAR/QSAR analysis - Shaowei Wang; Zhuoqi Chen; Xiya Ren; Chentao Ding; Xiulian Yang; Yunbing Tang; Ren-Shan Ge; Wei Chen; Yi Liu (Environmental Research, 2025)

Tectonic thickening in stagnant to mobile lid transition facilitated the stabilization of Archean cratons - Ning Ding; Chris Hawkesworth; Xiao-Lei Wang; Rong-Feng Ge; Axel Hofmann; Jun-Yong Li (Chemical Geology, 2025)

Maximum incremental reactivity for volatile organic compounds in three city clusters of China: quantification, variability, and implications for ozone control - Ming Wang; Yunlang Lu; Wenhao Ji; Wenxuan Chai; Hongli Wang; Feng Ding; Xin Zhao; Momei Qin; Yunjiang Zhang; Xinlei Ge; Min Shao (Atmospheric Environment, 2025)

Preparation of novel p-n heterogeneous Ag2O/MnO2 composites and photocatalytic degradation of gaseous toluene - Yao Ge; Yi Ding; Ranran Cheng; Yenan Yang; Xuan Wu; Xinyu Jia; Qifang Ren (Journal of Environmental Chemical Engineering, 2025)

Fabrication of bifunctional gold nanoparticles for self-calibration UV–Vis/surface-enhanced Raman spectroscopy dual-mode analysis of Hg2+ in milk - Jinxin Chen; Zhihong Wang; Miao Ding; Ying Gu; Kun Ge; Xuejing Fan (Food Chemistry, 2025)

Regulating factors and spatiotemporal patterns of terrestrial dissolved organic carbon adsorption in a high-turbidity estuary - Zhi Chen; Ricardo Torres; Jialing Yao; Ding He; Daidu Fan; Daniel Conley; Andrew Manning; Jianzhong Ge (Water Research, 2025)

MXene-based catalysts for water purification in the persulfate-based Fenton-like system - Mingmei Ding; Houzhen Zhou; Mingjing Ge; Zhiyun Jiang; Hang Xu; Xiaodong Jia; Emily Gao; Deepak Mallya; Li Gao (Journal of Water Process Engineering, 2025)

Effects of mulches on greenhouse gas emissions and soil microbial communities in cabbage production - Rong Liang; Lei Mei; Xuelian Fan; Jiangxing Wu; Mouliang Xiao; Yongfu Li; Jina Ding; Li Wang; Jaloliddin Shavkiev; David R. Chadwick; Davey Jones; Zhaofeng Yuan; et al. (Journal of Hazardous Materials, 2025)

Kinetic stability and transformation pathway of halogenated nitrophenols in drinking water - Jiacheng Ge; Xiaoyan Chen; Zhenqi Du; Yingying Zhou; Ruixin Qu; Jiangdong Cui; Shunke Ding; Wenhai Chu (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

The research progress of Ganoderma as a medicinal and edible product - Meilin Wang; Ding Li; Xu Gao; Xinze Wang; Li Zhang; Jiaxin Ding; Ke'er Xuan; Ge Wang; Yan Bai; Jian Gong (Food Bioscience, 2025)

Chitosan/kudzu-based packaging films synergistically reinforced by paeonol@ZIF-8 and Ag2CO3/Ag2O nano-heterojunctions for raspberry preservation - Xin Ding; Yiming Zhao; Xin Chen; Yanyan Huang; Zhihao Lin; Jing Wang; Ge Chen; Guangyang Liu; Xiaomin Xu; Bining Jiao; Xijuan Zhao; Donghui Xu (Food Packaging and Shelf Life, 2025)

Engineering covalent surface donor-acceptor interactions via Schiff base reaction for enhanced photocatalytic CO2 reduction - Jingyu Sun; Zhuowen Jiang; Guangying Nie; Lie Ding; Peiyan Wang; Chengsheng Ge; Shuaishuai Ma (Chemical Engineering Journal, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

In-situ secondary organic aerosol formation from ambient air in suburban Eastern China: Substantially distinct characteristics between summer and winter - Jibin Dou; Tengyu Liu; Dafeng Ge; Ying Zhang; Junchao Yin; Lei Wang; Haoyu Liu; Duzitian Li; Guangdong Niu; Liangduo Chen; Jiaping Wang; Ximeng Qi; et al. (Atmospheric Environment, 2025)

Spatial distribution and genesis of iron, manganese, arsenic, and nitrogen in groundwater of typical areas - Yanyan Li; Xiao Ge; Yifei Du; Hongrui Ding; Xiang Ji; Chuanye Zhou; Yuanyuan Chen; Di Cui; Anhuai Lu (Science China Earth Sciences, 2025)

Degradation-induced changes in soil nutrient availability alter leaf and root traits and their coordination in a riparian wetland ecosystem - Junxiang Ding; Ming Dou; Wenjing Ge; Yingshu Cao; Xiaoying Guo; Yue Yin; Guangsheng Zhou; Deliang Kong; Mei Liu (Plant and Soil, 2025)

The synergistic impact of cadmium and the wheat rhizosphere on the soil bacterial community in alkaline cropland in Northern China - Wenjing Ge; Fukun Gao; Jianlei Gao; Junxiang Ding; Long Han; Jing Wang; Tengyun Zhang; Hongli Li; Yixin Yan (Journal of Soils and Sediments, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

Genetic mapping of quantitative trait loci conferring resistance to race 4 of Xanthomonas campestris pv. campestris in cabbage (Brassica oleracea var. capitata) - Qingguo Sun; Liang Yan; Changjun Ge; Jinlan Li; Junfen Dai; Hao Ding (Physiological and Molecular Plant Pathology, 2025)

Towards clean energy technologies: Assessing the supply potential of critical rare earth elements in China - Han Ding; Jianping Ge (The Extractive Industries and Society, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Global warming likely compromises the annual performance of zero-energy buildings while the urban heat island effect exacerbates the impact - Yiman Zhao; Xiaotian Ding; Yifan Fan; Yongling Zhao; Jian Ge; Jan Carmeliet (Sustainable Cities and Society, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Hendersines J–M: Isoquinoline alkaloids from Corydalis hendersonii Hemsl. with cardiomyocyte protective and NO production inhibitory effects - Xiaochun Zhou; Zefeng Zhang; Changxin Liu; Shungang Jiao; Fuxing Ge; Qiuyuan Ding; Yiru Shen; Qiang Guo; Xingyun Chai (Phytochemistry, 2025)

Milk-derived exosome-loaded SS31 as a novel strategy to mitigate UV-induced photodamage in skin - Ding Luo; Yanhong Mao; Shengni Zhang; Shengqiang Shen; Xiaohu Ge; Litao Zhang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Wearable triboelectric Ag/thermoplastic polyurethane yarns with core-shell structure for energy harvesting and underwater sensing - Suya Hu; Zhenya Ge; Meng Chen; Peng Ding; Wei Zhai; Guoqiang Zheng; Kun Dai; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2025)

Locally hydrophobic and oxytropic nano-bio interface supports highly effective enzymatic catalysis: Mechanism and application for enzyme activity evaluation - Hanbing Ge; Jingxin Yu; Fengniu Lu; Zhiming Yang; Ding Cao; Zhiqin Yuan; Chao Lu (Chemical Engineering Journal, 2025)

Retraction notice to “Valorization of tropical fruits waste for production of commercial biorefinery products – A review” [Bioresour. Technol. 374 (2023) 128793] - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2025)

Retraction notice to “Production of biochar from tropical fruit tree residues and ecofriendly applications – A review” [Bioresour. Technol. 376 (2023) 128903] - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Myeloid-derived suppressor cells alleviate adverse ventricular remodeling after acute myocardial infarction - Yan-Ge Wang; Ding-Hang Wang; Wen-Hui Wei; Xin Xiong; Jing-Jing Wu; Zhan-Ying Han; Long-Xian Cheng (Molecular and Cellular Biochemistry, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Gypsum application increases microbial activity and organic carbon mineralization in saline paddy soils - Yixian Liu; Ze Zhang; Xiangxiang Wang; Ruiqiao Wu; Shuai Ding; Shuang Wang; Jianping Chen; Tida Ge; Zhenke Zhu (Applied Soil Ecology, 2025)

Corrigendum to ‘Facile synthesis of flower-cluster ZIF nanocarriers: Performance in controlled release of thiamethoxam and insecticidal activity’ [Environ. Res. 268 (2025) 120753] - Xin Ding; Kexin Yang; Xin Yang; Jie Zhou; Miao Wang; Zhihao Lin; Yaowei Zhang; Donghui Xu; Bining Jiao; Ge Chen; Xiaomin Xu; Lin Qin; et al. (Environmental Research, 2025)

Facile synthesis of flower-cluster ZIF nanocarriers: Performance in controlled release of thiamethoxam and insecticidal activity - Xin Ding; Kexin Yang; Xin Yang; Jie Zhou; Miao Wang; Zhihao Lin; Yaowei Zhang; Donghui Xu; Bining Jiao; Ge Chen; Xiaomin Xu; Lin Qin; et al. (Environmental Research, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

A TEMPO-anchored covalent organic framework towards high-performance lithium-oxygen batteries - Lili Liu; Keran Ge; Congcong Zhou; Meiying Kuai; Lanling Zhao; Yuntao Ding; Yuhui Chen; Weiwei Fang; Yuping Wu (Chemical Engineering Journal, 2025)

Atomically dispersed Ru-O3 anchored on the Ti3C2Tx surface with multiple reaction sites for the selective generation of single oxygen via peroxymonosulfate activation - Hang Xu; Mingjing Ge; Yin Liu; Chen Yao; Houzhen Zhou; Mingmei Ding; Yang Li (Chemical Engineering Journal, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Synergistic effect of microplastics and cadmium on microbial community and functional taxa in wheat rhizosphere soil - Jianhong Ji; Yingying Zhong; Mouliang Xiao; Xianting Wang; Zhi’e Hu; Mianjin Zhan; Jina Ding; Zhenke Zhu; Tida Ge (Soil Ecology Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

Large-scale rice mapping under spatiotemporal heterogeneity using multi-temporal SAR images and explainable deep learning - Ji Ge; Hong Zhang; Lijun Zuo; Lu Xu; Jingling Jiang; Mingyang Song; Yinhaibin Ding; Yazhe Xie; Fan Wu; Chao Wang; Wenjiang Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Microbiota dynamics and metabolic mechanisms in fermented sausages inoculated with Lactiplantibacillus plantarum and Staphylococcus xylosus - Yulong Yang; Gang Zhou; Yining Ding; Wenjing Shi; Yueqian Chen; Chunbo Ge; Baocai Xu; Liu Yang (Food Research International, 2025)

Assessing carbon storage in Xinjiang’s arid grassland Ecosystems: Insights from Process-Based modeling - Haiyan Han; Jianli Ding; Jinjie Wang; Annan Zeng; Xiangyu Ge; Xiaowen Zhu (CATENA, 2025)

An electrochemical sensor based on 2D Zn-MOFs and 2D C-Ti3C2Tx composite materials for rapid and direct detection of various foodborne pathogens - Liuhong Yang; Yifeng Ding; Yuhang Ma; Jing Wen; Jiafeng Wang; Ge Dai; Fengfeng Mo (Food Chemistry, 2025)

Antibacterial capacity and mechanism of the metabolites from two vaginal Lactobacillus strains - Jun Meng; Pan-Pan Dong; Xiang-Ge Xin; Yue Meng; Chang-He Ding; Jun Xi (Food Bioscience, 2025)

Sulfation of hyperbranched β-glucan from mushroom Pleurotus tuber-regium enhances α-glucosidase inhibition and anti-glycation properties - Lei Chen; Peipei Ge; Tong Zeng; Lanlan Zhao; Ka-Hing Wong; Guiyang Shi; Peter C.K. Cheung; Zhongyang Ding (Food Bioscience, 2025)

Enhanced removal of phenolic contaminants with permanganate oxidation mediated by SiO2@TEMPO: Performance, transformation pathway, and selectivity - Xiaoyan Chen; Jiangdong Cui; Xinyu Yang; Taoyue Yuan; Jiacheng Ge; Mengtao Ma; Shunke Ding; Wenhai Chu (Chemical Engineering Journal, 2025)

RETRACTED: Physicochemically protected organic carbon release is the rate-limiting step of rhizosphere priming in paddy soils - Cuiyan Wu; Wei Huang; Yixian Liu; Han Li; Shuai Ding; Zhenke Zhu; Feng Wang; Feike A. Dijkstra; Guangbin Zhang; Yakov Kuzyakov; Weiguo Cheng; Mouliang Xiao; et al. (Science of The Total Environment, 2024)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

A thermodynamics-based coupled model for multi-phase flowback in deformable dual-porosity shale gas reservoirs - Kai Wang; Shangqi Ge; Yue Ma; Wenjie Tan; Yizhe Hou; Yanxiao Si; Aizhong Ding; Xiao-Hui Chen (Journal of Hydrology, 2024)

Paraben preservatives exhibit inhibition on human and rat steroid 5α-reductase 1: A comprehensive 3D-QSAR and computational analysis - He Zhu; Chentao Ding; Yunbing Tang; Jingyi Zheng; Shaowei Wang; Zhongyao Ji; Yang Zhu; Ren-shan Ge; Huitao Li (Journal of Hazardous Materials, 2024)

Visible light-responsive TiO2-based hybrid nanofiller reinforced multifunctional chitosan film for effective fruit preservation - Ke Ding; Ying Xie; Haishan Xu; Saiqing Xu; Shuai Ge; Huan Li; Xia Chang; Jiani Chen; Rongrong Wang; Yang Shan; Shenghua Ding (Food Chemistry, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

The ABC1K gene family in Chinese cabbage: phylogeny, structure and function - Yuanxin Ye; Hengwu Ding; De Bi; Wen Ge; Jianke Yang; Shiyun Han; Sijia Zhang; Yuhong Liu; Xianzhao Kan (Genetic Resources and Crop Evolution, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Impact of axial segregation characteristics on the particle collision energy in rotating drums - Qiuhua Miao; Wenchang Zhu; Yifei Ding; Peng Huang; Chaobin Hu; Yang Ge (Minerals Engineering, 2024)

On-site monitoring and numerical simulation on groundwater flow and pollution plume evolution in a hexavalent-chromium contaminated site - Yong He; Ge-zhi Ou; Zhao Zhang; Zheng-tao Shen; He Wei; Xiang-hong Ding; Qiong Wang; Ke-neng Zhang; Yong-gui Chen; Wei-min Ye (Journal of Hazardous Materials, 2024)

Analysis of canopy interception characteristics and influencing factors in typical artificial forest in the Loess Plateau semi-arid region - Yuanhao Liu; Fei Wang; Shuyu Zhang; Wenbin Ding; Rongqi Li; Jianqiao Han; Wenyan Ge; Hao Chen; Shangyu Shi (Journal of Environmental Management, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Characterization of the Bacillus cereus spore killed by plasma-activated water (PAW) - Xiao Hu; Pengfei Ge; Xiaomeng Wang; Xinyu Liao; Jinsong Feng; Ruiling Lv; Tian Ding (Food Research International, 2024)

Navigating neighborhoods: Density, size, and species diversity influences on tree survival in subtropical secondary forests - Haonan Zhang; Fei Lu; Xiao Zheng; Jianing Xu; Yanyan Ni; Shuifei Chen; Xiaomin Ge; Yanming Fang; Yao Li; Ye Peng; Hui Ding (Forest Ecology and Management, 2024)

Simultaneous detection of eight dairy-derived components using multiplex PCR combined with gene membrane chip - Yafang Huang; Yingqiu Pan; Huili Xia; Xinyu Ma; Siling Ding; Jian Ge; Junfang Jiang; Feng Guan (Food Control, 2024)

Ocean acidification may alleviate the toxicity of zinc to the macroalga, Ulva lactuca - Jing Ma; Yuxin Xie; Zhouyue Lu; Houxu Ding; Wenjing Ge; Jie Jia; Juntian Xu (Marine Pollution Bulletin, 2024)

A WRF-UCM-SOLWEIG framework for mapping thermal comfort and quantifying urban climate drivers: Advancing spatial and temporal resolutions at city scale - Xiaotian Ding; Yongling Zhao; Dominik Strebel; Yifan Fan; Jian Ge; Jan Carmeliet (Sustainable Cities and Society, 2024)

Microbial carbon and phosphorus metabolism regulated by C:N:P stoichiometry stimulates organic carbon accumulation in agricultural soils - Xiangxiang Wang; Hongrui Zhang; Dan Cao; Cuiyan Wu; Xianting Wang; Liang Wei; Bin Guo; Shuang Wang; Jina Ding; Hao Chen; Jianping Chen; Tida Ge; et al. (Soil and Tillage Research, 2024)

Exploring the effects of environmentally relevant concentrations of tris(2-chloroethyl) phosphate on tadpole health: A comprehensive analysis of intestinal microbiota and hepatic transcriptome - Zi-Ying Wang; Wen-Qi Xie; Zi-Yong Xiang; Chi-Ying Zhang; Yi-Ge Xie; Roy You Chen Quah; Guo-Hua Ding (Science of The Total Environment, 2024)

Stabilizing methyl ferulate with nanosystem enhances its antifungal activity against Alternaria alternata in vitro and in vivo - Saiqing Xu; Shuai Ge; Ying Xie; Jing Cheng; Ke Ding; Huan Li; Hua Huang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

Insight into electricity production performance from dried waste activated sludge in dual chamber microbial fuel cells: Influencing factors, neural network modelling and microbial community analysis - Lin Wei; Ziyue Li; Tianqiu Hong; Yiming Tang; Ying Ge; Dongdong Ji; Qiang Zhang; Lei Luo; Jianyu Kong; Xiaoke Ding (Journal of Environmental Chemical Engineering, 2024)

The combination of metabolome and transcriptome clarifies the inhibition of the Alternaria toxin accumulation by methyl ferulate - Shuai Ge; Ying Xie; Ke Ding; Saiqing Xu; Haishan Xu; Xia Chang; Huan Li; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Food Chemistry, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

Integrated biomarker-based ecological risks assessment of tadpole responses to tris(2-chloroethyl) phosphate, tris(1-chloro-2-propyl) phosphate, and their combined environmental exposure - Wen-Qi Xie; Zi-Ying Wang; Yi-Ge Xie; Jia-Jun Hao; Xin-Dan Cao; Zi-Yong Xiang; Lu-Ping Lou; Guo-Hua Ding (Environmental Pollution, 2024)

Impact of urban form on building energy consumption in different climate zones of China - Yiman Zhao; Xiaotian Ding; Ziyu Wu; Shi Yin; Yifan Fan; Jian Ge (Energy and Buildings, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Citrus oil gland and cuticular wax inspired multifunctional gelatin film of OSA-starch nanoparticles-based nanoemulsions for preserving perishable fruit - Ying Xie; Ke Ding; Saiqing Xu; Haishan Xu; Shuai Ge; Xia Chang; Huan Li; Zijun Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Carbohydrate Polymers, 2024)

Enhancing soil particle content prediction accuracy: advanced hyperspectral analysis and machine learning models - Xiao Wang; Jianli Ding; Lijing Han; Jiao Tan; Xiangyu Ge (Journal of Soils and Sediments, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Exploring the cationic surfactant adsorption efficiency at concentrations relative to the critical micelle concentration by SA/SiO2 microspheres - Zhiying Li; Lei Zhao; Qing Ao; Ge Zhang; Dongqing Kang; Yingli Li; Jian Liu; Gongtao Ding; Zhongren Ma; Yeit Haan Teow; Mohd Shaiful Sajab; Zhiqiang Li; et al. (Journal of Environmental Management, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Long-term cover crops boost multi-nutrient cycling and subsurface soil carbon sequestration by alleviating microbial carbon limitation in a subtropical forest - Kai Ding; Liyao Chen; Yuting Zhang; Siyu Ge; Yiman Zhang; Meng Lu; Zhenming Shen; Zaikang Tong; Junhong Zhang (CATENA, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Comprehensive source identification of heavy metals in atmospheric particulate matter in a megacity: A case study of Hangzhou - Feili Li; Gaoxiang Zhang; Yifei Jinxu; Tianzheng Ding; Cong-Qiang Liu; Yunchao Lang; Nuohang Liu; Shuang Song; Yasheng Shi; Baozhu Ge (Journal of Environmental Management, 2024)

Conformational interlocking induced construction of hierarchically porous graphene membrane for ultrahigh-pressure sensing - Cong Liu; Hefeng Li; Jikang Zhao; Jiabao Zhu; Xianhua Huan; Yixuan Zhang; Ke Xu; Hongbo Geng; Xiaopeng Chen; Wenhui Ding; Lei Zu; Lei Ge; et al. (Chemical Engineering Journal, 2024)

Hierarchical Nash equilibrium seeking for optimal fault-tolerant formation control of networked MSVs in aggregative games - Yi-Fan Li; Ming-Feng Ge; Qian Chen; Teng-Fei Ding; Zhi-Wei Liu (Ocean Engineering, 2024)

Contamination characteristics of uncultivated arable lands and health risk warning based on the predicted heavy metal content in rice—Dongting Lake Basin, China - Chen Wu; Feng Li; Shengwei Yi; Xiangxi Ding; Yujun Wu; Fei Ge; Xionghui Ji; Yun Liu; Jiang Tian (Journal of Geochemical Exploration, 2024)

Microbial treatment of waste crumb rubber: Reducing energy consumption and harmful emissions during asphalt production process - Juan Xie; Xucheng Zhao; Yongnan Liu; Dongdong Ge; Shifeng Wang; Zheyu Ding; Songtao Lv (Journal of Cleaner Production, 2024)

Central Asia's desertification challenge: Recent trends and drives explored with google earth engine - Shuang Zhao; Jianli Ding; Jinjie Wang; Xiangyu Ge; Lijing Han; Ruimei Wang; Shaofeng Qin (Journal of Cleaner Production, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Long-term cover crop monocultures and mixtures improve soil multifunctionality and shift microbial communities and functions - Kai Ding; Yuting Zhang; Siyu Ge; Yiman Zhang; Meng Lu; Zhenming Shen; Zaikang Tong; Junhong Zhang (European Journal of Agronomy, 2024)

Toxicity comparison and risk assessment of two chlorinated organophosphate flame retardants (TCEP and TCPP) on Polypedates megacephalus tadpoles - Yi-Ge Xie; Zi-Ying Wang; Wen-Qi Xie; Zi-Yong Xiang; Xin-Dan Cao; Jia-Jun Hao; Guo-Hua Ding (Aquatic Toxicology, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Comparative study of terramechanics properties of spherical and cylindrical feet for planetary legged robots on deformable terrain - Huaiguang Yang; Chu Zhang; Liang Ding; Qingqing Wei; Haibo Gao; Guangjun Liu; Liyuan Ge; Zongquan Deng (Journal of Terramechanics, 2024)

Construction of CuFe2O4/Bi2MoO6 heterogeneous catalyst for high-efficiency photocatalytic degradation of levofloxacin under visible light: Mechanism, pathways and DFT calculation - Xinyu Jia; Shilong Xu; Qinglin Huang; Haixia Ji; Yao Ge; Yenan Yang; Qifang Ren; Shaohua Chen; Zhen Jin; Yi Ding (Journal of Environmental Chemical Engineering, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

Decoding a novel green and effective antimicrobial agent: Glycerol monolaurate stable in nanosystem - Saiqing Xu; Xia Chang; Haishan Xu; Ying Xie; Shuai Ge; Yanqun Xu; Zisheng Luo; Yang Shan; Shenghua Ding (Food Control, 2024)

Factors driving antimony accumulation in soil-pakchoi and wheat agroecosystems: Insights and predictive models - Tongliang Wu; Naichi Zhang; Cun Liu; Changfeng Ding; Peng Zhang; Sainan Hu; Yihang Huang; Zixuan Ge; Peixin Cui; Yujun Wang (Environmental Pollution, 2024)

Machine learning elucidates ubiquity of enhanced ozone air pollution in China linked to the spring festival effect - Baizhen Zhu; Jie Fang; Yunjiang Zhang; Jian Qiu; Kehong Chen; Kexin Zhang; Hongwei Liang; Han Yang; Yihua Ding; Xinlei Ge (Atmospheric Pollution Research, 2024)

Utilizing fMRI to Guide TMS Targets: the Reliability and Sensitivity of fMRI Metrics at 3 T and 1.5 T - Qiu Ge; Matthew Lock; Xue Yang; Yuejiao Ding; Juan Yue; Na Zhao; Yun-Song Hu; Yong Zhang; Minliang Yao; Yu-Feng Zang (Neuroinformatics, 2024)

Reducing the accumulation of cadmium and phenanthrene in rice by optimizing planting spacing: Role of low-abundance but core rhizobacterial communities - Chen Wu; Yujun Wu; Feng Li; Xiangxi Ding; Shengwei Yi; Sicheng Hang; Fei Ge; Ming Zhang (Science of The Total Environment, 2024)

Maintaining the balance of fungal community through active packaging film makes strawberry fruit pose pleasant flavor during storage - Haishan Xu; Qi Quan; Xia Chang; Shuai Ge; Saiqing Xu; Rongrong Wang; Yanqun Xu; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Investigation on the budget of peroxyacetyl nitrate (PAN) in the Yangtze River Delta: Unravelling local photochemistry and regional impact - Tao Xu; Wei Nie; Zheng Xu; Chao Yan; Yuliang Liu; Qiaozhi Zha; Ruoxian Wang; Yuanyuan Li; Lei Wang; Dafeng Ge; Liangduo Chen; Ximeng Qi; et al. (Science of The Total Environment, 2024)

Effects of microplastics on photosynthesized C allocation in a rice-soil system and its utilization by soil microbial groups - Zhi’e Hu; Mouliang Xiao; Jialing Wu; Yaoyao Tong; Jianhong Ji; Qing Huang; Fan Ding; Jina Ding; Zhenke Zhu; Jianping Chen; Tida Ge (Journal of Hazardous Materials, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Coordination of leaf and root economic space in alpine coniferous forests on the Tibetan Plateau - Junxiang Ding; Qitong Wang; Wenjing Ge; Qing Liu; Deliang Kong; Huajun Yin (Plant and Soil, 2024)

Prediction of SBRT response in liver cancer by combining original and delta cone-beam CT radiomics: a pilot study - Pengfei Yang; Jingjing Shan; Xin Ge; Qinxuan Zhou; Mingchao Ding; Tianye Niu; Jichen Du (Physical and Engineering Sciences in Medicine, 2024)

Variations in life history parameters, population dynamics, and transcriptome regulation of Brachionus plicatilis exposed to triclosan - YunhongYang; Tianyue Mao; Yifan Ding; Lingling Ge; Lei Feng; Meng Cai; Cui Han; Jiaxin Yang (Marine Pollution Bulletin, 2024)

Retrieving hourly seamless PM2.5 concentration across China with physically informed spatiotemporal connection - Yu Ding; Siwei Li; Jia Xing; Xi Li; Xin Ma; Ge Song; Mengfan Teng; Jie Yang; Jiaxin Dong; Shiyao Meng (Remote Sensing of Environment, 2024)

Integrated transcriptomic, proteomic, and metabolomic approaches reveal the antifungal mechanism of methyl ferulate against Alternaria alternate - Hui Kong; Shuai Ge; Xia Chang; Saiqing Xu; Haishan Xu; Xincheng Fu; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Contrasting effects of maize straw and its biochar on aggregation and soil organic matter stabilization - Dechang Ji; Liwei Ge; Lukas Van Zwieten; Tingting An; Shuangyi Li; Yakov Kuzyakov; Fan Ding; Jingkuan Wang (Plant and Soil, 2024)

Continuous cropping disorders of eggplants (Solanum melongena L.) and tomatoes (Solanum lycopersicum L.) in suburban agriculture: Microbial structure and assembly processes - Zufei Xiao; Changyi Lu; Zhiyong Wu; Xinyuan Li; Kai Ding; Zhe Zhu; Ruixia Han; Junyi Zhao; Tida Ge; Gang Li; Yong-Guan Zhu (Science of The Total Environment, 2024)

Time-resolved alkali release during steam gasification of char in a fixed bed reactor - Saiman Ding; Yaxin Ge; Efthymios Kantarelis; Xiangrui Kong; Jan B.C. Pettersson; Klas Engvall (Fuel, 2024)

Efficient degradation of ciprofloxacin in wastewater by CuFe2O4/CuS photocatalyst activated peroxynomosulfate - Xinyu Jia; Jinhui Zhang; Qinglin Huang; Chunyu Xiong; Haixia Ji; Qifang Ren; Zhen Jin; Shaohua Chen; Wanmi Guo; Jing Chen; Yao Ge; Yi Ding (Environmental Research, 2024)

Exploring the influence of sludge dewatering agents on Microplastic aging under hydrothermal treatment: Insights from Polylactic Acid microplastics - Yang Yu; Yindi Ding; Chenjia Miao; Xi Yang; Shifu Ge (Environmental Research, 2024)

Effects of biochar and volcanic rock addition on humification and microbial community during aerobic composting of cow manure - Shuangshuang Ma; Yujun Shen; Jingtao Ding; Hongsheng Cheng; Haibin Zhou; Mianshen Ge; Jian Wang; Qiongyi Cheng; Dongli Zhang; Yun Zhang; Pengxiang Xu; Pengyue Zhang (Bioresource Technology, 2024)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Impacts of fresh bed materials on alkali release and fuel conversion rate during wood pyrolysis and char gasification - Yaxin Ge; Saiman Ding; Wennan Zhang; Xiangrui Kong; Efthymios Kantarelis; Klas Engvall; Jan B.C. Pettersson (Fuel, 2023)

Design and fabrication of Zn@ZnO@Ag chip for Raman scattering analysis of norfloxacin in liquid milk, fish and animal feeds - Hanqiang Zhang; Xuejing Fan; Yangyue Ding; Lunzhao Yi; Kun Ge; Ying Gu (Food Chemistry, 2023)

Experimental study and theoretical analysis of the shear behavior of single-box double-chamber steel-bamboo composite beams - Jingshu Ding; Xuan Wang; Yumeng Ge; Zhenwen Zhang; Yushun Li (Engineering Structures, 2023)

A personalized regression model for predicting thermal sensation based on local skin temperature in moderate summer conditions - Yun Qi; Rui Wang; Chaoyi Zhao; Chao Ding; Chenqiu Du; Jiazheng Zhang; Xuan Zhang; Xinchang Chen; Mingjie Zhang; Qingfeng Bie; Meng Ge (Energy and Buildings, 2023)

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Urban surface classification using semi-supervised domain adaptive deep learning models and its application in urban environment studies - Xiaotian Ding; Yifan Fan; Yuguo Li; Jian Ge (Environmental Science and Pollution Research, 2023)

Impacts of poly(lactic acid) microplastics on organic compound leaching and heavy metal distribution during hydrothermal treatment of sludge - Yang Yu; Bingxing Zhu; Yindi Ding; Cailing Zhou; Shifu Ge (Science of The Total Environment, 2023)

Non-invasive prediction of mango quality using near-infrared spectroscopy: Assessment on spectral interferences of different packaging materials - Fangchen Ding; Changzhou Zuo; Juan Francisco García-Martín; Yan Ge; Kang Tu; Jing Peng; Hongmei Xiao; Weijie Lan; Leiqing Pan (Journal of Food Engineering, 2023)

Structural optimization of solar thermoelectric generators considering thermal stress conditions - Minghui Ge; Zhiwei Xuan; Xionglei Liu; Ding Luo; Yulin Wang; Yanzhe Li; Yulong Zhao (Journal of Cleaner Production, 2023)

A new nanohybrid particle reinforced multifunctional active packaging film for efficiently preserving postharvest fruit - Haishan Xu; Qi Quan; Xia Chang; Shuai Ge; Saiqing Xu; Rongrong Wang; Yanqun Xu; Zisheng Luo; Yang Shan; Shenghua Ding (Food Hydrocolloids, 2023)

Understory vegetation restoration improves soil physicochemical properties, enzymatic activity, and changes diazotrophic communities in Cunninghamia lanceolata plantations but depends on site history - Kai Ding; Yuting Zhang; Anna Yang; Yiman Zhang; Meng Lu; Siyu Ge; Yongbin Qiu; Junhong Zhang; Zaikang Tong (Plant and Soil, 2023)

Transport model simulation prediction and environmental risk assessment of pyrethroid insecticides in urban artificial lakes caused by rainfall: A case study of Cloud Mountain Park in subhumid climate zone - Siyao Liu; Xuanying Li; Rui Ding; Yuwen Pan; Xiaoyu Ge; Weifang Ma (Journal of Environmental Management, 2023)

Effect of pore-throat structure on air-foam flooding performance in a low-permeability reservoir - Guangfeng Liu; Yaping Ding; Juntao Wang; Lizhen Ge; Xiaoming Chen; Daoyong Yang (Fuel, 2023)

Rapid detection of foodborne pathogens in diverse foodstuffs by universal electrochemical aptasensor based on UiO-66 and methylene blue composites - Ge Dai; Handong Yao; Liuhong Yang; Yifeng Ding; Shuxin Du; Hui Shen; Fengfeng Mo (Food Chemistry, 2023)

Dual Förster resonance energy transfer effects enables high photocurrent density and high fill factor in ternary organic solar cells - Hongqian Wang; Daobin Yang; Pengfei Ding; Lin Xie; Zhenyu Chen; Shuncheng Yang; Pengyu Yan; Yuanyuan Meng; Jianqi Zhang; Zhixiang Wei; Ziyi Ge (Chemical Engineering Journal, 2023)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Morphological and architectural evolution of submarine channels: An example from the world's largest submarine fan in the Bay of Bengal - Dongwei Li; Chenglin Gong; Guozhang Fan; Ronald J. Steel; Daoyao Ge; Dali Shao; Liangbo Ding (Marine and Petroleum Geology, 2023)

Exploring the inter-decadal variability of soil organic carbon in China - Zipeng Zhang; Jianli Ding; Chuanmei Zhu; Jinjie Wang; Xiang Li; Xiangyu Ge; Lijing Han; Xiangyue Chen; Jingzhe Wang (CATENA, 2023)

Piezo2 Channel Upregulation is Involved in Mechanical Allodynia in CYP-Induced Cystitis Rats - Lei Liu; Yan Zhao; Wenhan An; Mengmeng Zhao; Ning Ding; Hanwen Liu; Nan Ge; Jiliang Wen; Xiulin Zhang; Shulu Zu; Wendong Sun (Molecular Neurobiology, 2023)
Mechanical sensing Piezo2 channel in primary sensory neurons has been shown contribute to mechanical allodynia in somatic chronic pain conditions. Interstitial cystitis (IC)-associated pain is often triggered by bladder filling, a presentation that mimics the mechanical allodynia. In the present study, we aimed to examine the involvement of sensory Piezo2 channel in IC-associated mechanical allodynia using a commonly employed cyclophosphamide (CYP)-induced IC model rat. Piezo2 channels in dorsal root ganglia (DRGs) was knocked down by intrathecal injections of Piezo2 anti-sense oligodeoxynucleotides (ODNs) in CYP-induced cystitis rats, and mechanical stimulation–evoked referred bladder pain was measured in the lower abdomen overlying the bladder using von Frey filaments. Piezo2 expression at the mRNA, protein, and functional levels in DRG neurons innervating the bladder was detected by RNA-fluorescence in situ hybridization, western blotting, immunofluorescence, and Ca 2+ imaging, respectively. We found that Piezo2 channels were expressed on most (> 90%) of the bladder primary afferents, including afferents that express CGRP, TRPV1 and stained with isolectin B4. CYP-induced cystitis was associated with Piezo2 upregulation in bladder afferent neurons at the mRNA, protein, and functional levels. Knockdown of Piezo2 expression in DRG neurons significantly suppressed mechanical stimulation–evoked referred bladder pain as well as bladder hyperactivity in CYP rats compared to CYP rats treated with mismatched ODNs. Our results suggest upregulation of Piezo2 channels is involved in the development of bladder mechanical allodynia and bladder hyperactivity in CYP-induced cystitis. Targeting Piezo2 might be an attractive therapeutic approach for IC-related bladder pain.

Distribution of microplastics in soil aggregates after film mulching - Yuhuai Liu; Yingying Zhong; Can Hu; Mouliang Xiao; Fan Ding; Yongxiang Yu; Huaiying Yao; Zhenke Zhu; Jianping Chen; Tida Ge; Jina Ding (Soil Ecology Letters, 2023)

Microplastics affect activity and spatial distribution of C, N, and P hydrolases in rice rhizosphere - Yaoyao Tong; Jina Ding; Mouliang Xiao; Muhammad Shahbaz; Zhenke Zhu; Ming Chen; Yakov Kuzyakov; Yangwu Deng; Jianping Chen; Tida Ge (Soil Ecology Letters, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Evaluating the effects of single and integrated extreme climate events on hydrology in the Liao River Basin, China using a modified SWAT-BSR model - Yingqi Zhang; Jianing Ge; Junyu Qi; Haipeng Liu; Xueliang Zhang; Gary W. Marek; Chengcheng Yuan; Beibei Ding; Puyu Feng; De Li Liu; Raghavan Srinivasan; Yong Chen (Journal of Hydrology, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

Genetic response of Salmonella Typhimurium to trans-cinnamaldehyde assisted heat treatment and its correlation with bacterial resistance in different low moisture food components - Qiao Ding; Chongtao Ge; Robert C. Baker; Robert L. Buchanan; Rohan V. Tikekar (Food Microbiology, 2023)

An ultrafast H* migration channel and oxidation activity driven by multifunctional Co atoms on twin Co0.01Mn0.29Cd0.7S homojunction surface for photocatalytic overall water splitting - Wei Tang; Tianbiao Zeng; Liguo Zhang; Baozhen Li; Ge Wang; Xueqing Xing; Yihong Ding; Changmin Hou; Wenjun Dong (Chemical Engineering Journal, 2023)

Multi-scale risk assessment and mitigations comparison for COVID-19 in urban public transport: A combined field measurement and modeling approach - Yinshuai Feng; Yan Zhang; Xiaotian Ding; Yifan Fan; Jian Ge (Building and Environment, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Benfotiamine attenuates the high-carbohydrate diet-induced mitochondrial redox imbalance in fish Megalobrama amblycephala by activating SIRT3 - Ling Zhang; Ya-Ping Ge; Yang-Yang Huang; Wei-Liang Chen; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li (Aquaculture, 2023)

Forest conversion from pure to mixed Cunninghamia lanceolata plantations enhances soil multifunctionality, stochastic processes, and stability of bacterial networks in subtropical southern China - Kai Ding; Yuting Zhang; Li Wang; Siyu Ge; Yiman Zhang; Qi Yang; Huahong Huang; Zaikang Tong; Junhong Zhang (Plant and Soil, 2023)

Tectonic nature, subduction, and closure of the Mudanjiang Ocean: Insights from newly discovered oceanic fragments in the Luobei Heilongjiang Complex - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Xin Ding; Zheng Ji; Yan-Long Zhang; Yu Dong; Wen-chun Ge (Lithos, 2023)

Assessment of trans-cinnamaldehyde and eugenol assisted heat treatment against Salmonella Typhimurium in low moisture food components - Qiao Ding; Chongtao Ge; Robert C. Baker; Robert L. Buchanan; Rohan V. Tikekar (Food Microbiology, 2023)

ATP-induced hypothermia improves burn injury and relieves burn pain in mice - Yang Zhao; Junhao Liu; Zhao Ding; Wenhao Ge; Shiming Wang; Jianfa Zhang (Journal of Thermal Biology, 2023)

Transcriptomics and gas chromatography-mass spectrometry metabolomics reveal the mechanism of heat shock combined with 1-methylcyclopropene to regulate the cuticle wax of jujube fruit during storage - Shuai Ge; Rongrong Wang; Lvzhu Yang; Hui Kong; Xia Chang; Xincheng Fu; Yang Shan; Shenghua Ding (Food Chemistry, 2023)

RETRACTED: Production of biochar from tropical fruit tree residues and ecofriendly applications – A review - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2023)

Online monitoring of alkali release during co-pyrolysis/gasification of forest and agricultural waste: Element migration and synergistic effects - Yaxin Ge; Saiman Ding; Xiangrui Kong; Efthymios Kantarelis; Klas Engvall; Jan B.C. Pettersson (Biomass and Bioenergy, 2023)

Netrin-3 Suppresses Diabetic Neuropathic Pain by Gating the Intra-epidermal Sprouting of Sensory Axons - Weiping Pan; Xueyin Huang; Zikai Yu; Qiongqiong Ding; Liping Xia; Jianfeng Hua; Bokai Gu; Qisong Xiong; Hualin Yu; Junbo Wang; Zhenzhong Xu; Linghui Zeng; et al. (Neuroscience Bulletin, 2023)

Whole genome evaluation analysis and preliminary Assembly of Oratosquilla oratoria (Stomatopoda: Squillidae) - Xiaoli Sun; Gang Wang; Jie Yang; Wei Yu; Jiayue Xu; Boping Tang; Ge Ding; Daizhen Zhang (Molecular Biology Reports, 2023)

Microbial coexistence in the rhizosphere and the promotion of plant stress resistance: A review - Jiaqi Ge; Dong Li; Jixian Ding; Xian Xiao; Yuting Liang (Environmental Research, 2023)

An ultrasensitive three-dimensional structured multi-mode sensor for out-of-plane forces - Li Ding; Dinghao Wu; Yanjie Wei; Siyong Liu; Ge He; Xinglong Gong; Dongsheng Zhang (Chemical Engineering Journal, 2023)

RETRACTED: Valorization of tropical fruits waste for production of commercial biorefinery products – A review - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2023)

Machine learning-assisted mapping of city-scale air temperature: Using sparse meteorological data for urban climate modeling and adaptation - Xiaotian Ding; Yongling Zhao; Yifan Fan; Yuguo Li; Jian Ge (Building and Environment, 2023)

Effect of fresh bed materials on alkali release and thermogravimetric behavior during straw gasification - Yaxin Ge; Saiman Ding; Wennan Zhang; Xiangrui Kong; Klas Engvall; Jan B.C. Pettersson (Fuel, 2023)

Landslide susceptibility mapping and dynamic response along the Sichuan-Tibet transportation corridor using deep learning algorithms - Wubiao Huang; Mingtao Ding; Zhenhong Li; Junchuan Yu; Daqing Ge; Qi Liu; Jing Yang (CATENA, 2023)

Extreme wind speed prediction in mountainous area with mixed wind climates - Teng Ma; Wei Cui; Lin Zhao; Ding Yejun; Fang Genshen; Yaojun Ge (Stochastic Environmental Research and Risk Assessment, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

Assessment of future flood risk induced by sea level rise and tropical cyclones under global warming in the Xiamen Bay, Fujian, China - Wenyun Guo; Ding Yao; Zhi Chen; Pingxing Ding; Jianzhong Ge (Frontiers in Marine Science, 2023)
Tropical cyclone (TC)-induced coastal flooding can lead to severe hazards in low-lying lands and is expected to be exacerbated by sea level rise and TC climatology changes related to the warming climate. Since the dense population in Xiamen Bay, Fujian, China, it is highly valuable in understanding coastal flooding of it, but little studies involved this topic. In this study, we establish a high-resolution numerical model covering all coastal low-lying land in Xiamen Bay based on FVCOM. This model is then used to assess the flood risk in Xiamen Bay under TCs with 10-, 100-, and 1000-year pressures by applying a multi-tracks blend method. The results show that 126 km 2 of low-lying area can be flooded periodically by astronomical tides; and 388, 504, and 598 km 2 of low-lying area can be flooded under TCs with 10-, 100-, and 1000-year pressures, accompanied by increased average flood depths of 2.3, 2.8, and 3.4 m, respectively. By 2100 under SSP5-8.5, the well-protected Xiamen Island becomes impacted by TCs with 10-year pressure, and flood areas under TCs with 100-year pressure are estimated to be nearly equivalent to that under TCs with 1000-year pressure at the current climate. The most increased exposure area by climate change are artificial surfaces and agricultural areas, showing the potential higher flood disasters in future.

Differences in Thermo-Rheological Structure between Qiongdongnan Basin and Pearl River Mouth Basin: Implications for the Extension Model in the Northwestern Margin of the South China Sea - Chaoyang Li; Pengyao Zhi; Renwei Ding; Lihong Zhao; Wei Gong; Zhonghua Li; Jiayu Ge (Journal of Marine Science and Engineering, 2023)
This study combines surface heat flow, multi-channel seismic reflection profiles, and ocean-bottom seismometer (OBS) profiles to determine the thermo-rheological structure of the Qiongdongnan Basin (QDNB) and Pearl River Mouth Basin (PRMB), with the aim of researching the west–east variation of the passive continental margin rifting. Based on the initial lithospheric rheological model of a jelly sandwich-1 (JS-1) regime, the current architecture of the continental margin is identified to be the result of a non-uniform extension. Due to the decoupled crust–mantle relationship caused by the weak lower crust, the non-uniform extension led to the rupture of the mantle lithosphere before the crust. The central Xisha Trough falls into the JS-2 regime with only one brittle load layer, which is close to the rigid oceanic lithosphere of the Northwest Sub-basin (NSB). The high-velocity layers (HVLs) and detachment faults beneath the Xisha Trough are considered to be the result of the cooling of a thinned lower crust with mantle underplating during the middle stage of continental margin rifting. A seaward-increasing trend of lithospheric rheological strength is exhibited across the PRMB, from the crème brûlée-1 (CB-1) regime at the continental shelf to the JS-2 regime at the NSB. Unlike the HVLs of the Xisha Trough, the lower crustal HVLs beneath the eastern PRMB formed during the late stage of continental margin rifting due to the mantle lateral flow. The absence of HVLs beneath the western PRMB may indicate that the mantle lateral flow demonstrates a limited impact.

Full-scale experimental and numerical study of smoke spread characteristics in a long-closed channel with one lateral opening - Weixin Tong; Fanliang Ge; Long Ding; Jie Ji; Yuanlong Zhou; Yang Zhou; Fan Zhou (Tunnelling and Underground Space Technology, 2023)

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Introducing water factors improves simulations of maize stomatal conductance models under plastic film mulching in arid and semi-arid irrigation areas - Cheng Li; Naijiang Wang; Xiaoqi Luo; Yue Li; Tibin Zhang; Dianyuan Ding; Qin'ge Dong; Hao Feng; Wenxin Zhang (Journal of Hydrology, 2023)

Anti-inflammatory effects of extracellular vesicles from Morchella on LPS-stimulated RAW264.7 cells via the ROS-mediated p38 MAPK signaling pathway - Qi Chen; Chengchuan Che; Shanshan Yang; Pingping Ding; Meiru Si; Ge Yang (Molecular and Cellular Biochemistry, 2023)
Morchella is a kind of important edible and medicinal fungi, which is rich in polysaccharides, enzymes, fatty acids, amino acids and other active components. Extracellular vesicles (EVs) have a typical membrane structure, and the vesicles contain some specific lipids, miRNAs and proteins, and their can deliver the contents to different cells to change their functions. The present study investigated whether Morchella produce extracellular vesicles and its anti-inflammatory effect on lipopolysaccharide (LPS)-induced RAW246.7 macrophages. The experimental results showed that Morchella produced extracellular vesicles and significantly reduced the production of nitric oxide (NO) and reactive oxygen species (ROS) in a model of LPS-induced inflammation. In addition, the expression of inflammatory factor-related genes such as inducible nitric oxide synthase (iNOS), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and cyclooxygenase-2 (COX-2) showed dose-dependent inhibition. Morchella extracellular vesicles also can inhibit the inflammatory response induced by LPS by inhibiting the production of ROS and reducing the phosphorylation levels of the p38 MAPK signaling pathway. These results indicate that the Morchella extracellular vesicles can be used as a potential anti-inflammatory substance in the treatment of inflammatory diseases.

The Characteristics of Solanum lycopersicum SlSPRH1 and its Negative Role in Thermotolerance in Arabidopsis - Haidong Ding; Qihui Xie; Yurong Ji; Lu Qian; Yali Guan; Cailin Ge (Journal of Plant Growth Regulation, 2023)

New record of explosive warmings in East Antarctica - Sai Wang; Minghu Ding; Ge Liu; Shoudong Zhao; Wenqian Zhang; Xichen Li; Wen Chen; Cunde Xiao; Dahe Qin (Science Bulletin, 2023)

Mechanism of iron doping promoting high temperature deNOx and anti-water vapor and SO2 poisoning of ZrW(Fe)Ox - Zhanzhi Ge; Yan Ding; Xinqi Huang; Yuesong Shen (Fuel, 2023)

Aging of polylactic acid microplastics during hydrothermal treatment of sewage sludge and its effects on heavy metals adsorption - Yang Yu; Yindi Ding; Cailing Zhou; Shifu Ge (Environmental Research, 2023)

The Pseudogene BMEA_B0173 Deficiency in Brucella melitensis Contributes to M-epitope Formation and Potentiates Virulence in a Mice Infection Model - Ge Zhang; Hao Dong; Yu Feng; Hui Jiang; Tonglei Wu; Jiali Sun; Xin Wang; Minghe Liu; Xiaowei Peng; Yinghui Zhang; Xiaoqian Zhang; Liangquan Zhu; et al. (Current Microbiology, 2022)

Measuring Bed Exchange Properties of Cohesive Sediments Using Tripod Data - Zaiyang Zhou; Jianzhong Ge; Dirk Sebastiaan van Maren; Jinghua Gu; Pingxing Ding; Zhengbing Wang (Journal of Marine Science and Engineering, 2022)
The Krone–Partheniades (K-P) framework has been used for decades to quantify and analyze the sediment exchange at a water–bed interface. Measuring the erosion and deposition parameters that are part of this framework requires time-consuming field observations. Additionally, the erosion parameters are measured independently of deposition parameters, while in reality they are coupled. In numerical models applying the K-P framework these parameters are often assumed to be constant in time and mutually independent. In this study, we develop a relatively simple methodology to determine the erosion and deposition parameters, using conventional near-bed observations of bed level, sediment concentration and flow velocity. This methodology is subsequently applied to tripod observations collected in the Changjiang estuary, China, to compute continuous time-varying erosion and settling parameters. We propose a diagram to visualize the interdependency and accuracy of erosion and deposition parameters, which is the input for K-P framework models requiring this interdependency.

Assessment of the inhalation exposure and incremental lifetime cancer risk of PM2.5 bounded polycyclic aromatic hydrocarbons (PAHs) by different toxic equivalent factors and occupancy probability, in the case of Xi’an - Yumeng Wang; Zedong Wang; Jingzhi Wang; Runyu Wang; Xinxin Ding; Neil McPherson Donahue; Zhibao Dong; Ge Ma; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2022)

On the drivers of temperature extremes on the Antarctic Peninsula during austral summer - Sai Wang; Minghu Ding; Ge Liu; Ting Wei; Wenqian Zhang; Wen Chen; Tingfeng Dou; Cunde Xiao (Climate Dynamics, 2022)

An Efficient Approach to Determine the Shear Damage Zones of Rock Joints Using Photogrammetry - Ding Xia; Cheng He; Huiming Tang; Yunfeng Ge; Junwei Ma; Junrong Zhang (Rock Mechanics and Rock Engineering, 2022)

Plant Growth Stimulating Bacteria and Filter Mud Cake Enhance Soil Quality and Productivity of Mango (Mangifera indica L.) - Yu Ge; Arwa Abdulkreem AL-Huqail; Zhaoxi Zhou; Esmat F. Ali; Adel M. Ghoneim; Mamdouh Eissa; Mahmoud S. El-Sharkawy; Zheli Ding (Journal of Soil Science and Plant Nutrition, 2022)

Formation and Breakdown of an Offshore Summer Cold-Water Zone and Its Effect on Phytoplankton - Weiqi Li; Xiangqian Zhou; Jianzhong Ge; Pingxing Ding; Dongyan Liu (Frontiers in Marine Science, 2022)
Estuarine plume frontal zones typically form a vertical two-layer structure with low-salinity and a high-temperature plume during the summertime. However, two field surveys in the Changjiang River Estuary and its adjacent shelf waters identified a significant surface cold-water zone (CWZ) formation in the summers of 2014 and 2015. The sea surface temperature of the CWZ was 4°C lower than the multi-year summer average. Satellite images showed that the CWZ mainly appeared in the Yangtze Shoal during the periods of July 1–17, 2014, and July 3–19, 2015. A three-dimensional physical-biogeochemical coupled model was used to explore the formation mechanism of the CWZ. Our investigation revealed that an uncharacteristic northerly wind during the southerly monsoon resulted in a significant onshore retreat of the plume front. Vertical tidal mixing is stronger than the decreased stratification in the former plume-covered region, which resulted in the formation of the CWZ. This process was accompanied by relatively lower net heat flux, which also promoted CWZ formation. The formation of CWZ had a strong ecological impact; enhanced vertical mixing transported nutrients from the lower layer to the surface column, relaxing the CWZ’s phosphate limitation. CWZ formation also increased the depth of the mixed layer and turbidity level in the water column, forming a temporary light limitation in the center. At the margin of the CWZ, it formed a patch with a high concentration of chlorophyll a . The underwater light was sufficient once the plume was restored and the CWZ was stratified again, and the phytoplankton grew rapidly in the center of the CWZ.

Regulation of OsLPR1 gene on the formation of rice root iron plaque under low phosphorus - Yan Ding; Menglian Ren; Shuangrong Mo; Jing Liu; Zegang Wang; Cailin Ge; Yulong Wang (Plant Biotechnology Reports, 2022)

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Influences of the 1855 AD Huanghe (Yellow River) Relocation on Sedimentary Organic Carbon Burial in the Southern Yellow Sea - Jianying Liu; Da-Wei Li; Yang Ding; Tiantian Ge; Weifang Chen; Chih-An Huh; Meixun Zhao (Frontiers in Marine Science, 2022)
The Huanghe (Yellow River) supplies large amount of sediments and terrestrial organic carbon (OC) to the eastern Chinese marginal seas. A relocation of the Huanghe outlet from the southern Yellow Sea (YS) to the Bohai Sea occurred in 1855 AD, however, detailed knowledge about the impact of this relocation on sedimentary source and OC burial in Chinese marginal seas is still critically lacking. In this study, we present total OC content and its isotope (δ 13 C), along with bulk total organic carbon (TOC)/total nitrogen (TN) molar ratio and lipid biomarker contents, in a sediment core HH12 from the southern YS with sediment age spanning the last 300 years. We find that TOC and terrestrial lipid biomarker mass accumulation rates were lower between 1855 AD and 1950 AD than that prior to 1855 AD in core HH12; and in accordance, both TOC/TN ratio and δ 13 C records indicate a gradual decrease of terrigenous source contributions to sedimentary OC. This suggests that the relocation of the Huanghe outlet reduced the transport of terrestrial OC to the southern YS. However, the δ 13 C record also indicates a relative increase of terrestrial OC contribution to sedimentary OC after 1950 AD, and the most likely explanation is increased contributions from the old Huanghe delta erosion and Korean rivers. Future studies should focus on better constraining the variations of terrestrial and marine endmembers with δ 13 C and Δ 14 C analyses of specific biomarkers to examine these linkages.

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Retraction Note to: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2021)

Effects of Dual Fronts on the Spatial Pattern of Chlorophyll-a Concentrations in and off the Changjiang River Estuary - Weiqi Li; Jianzhong Ge; Pingxing Ding; Jianfei Ma; Patricia M. Glibert; Dongyan Liu (Estuaries and Coasts, 2021)

Mechanism of Low Phosphorus Inducing the Main Root Lengthening of Rice - Yan Ding; Zegang Wang; Shuangrong Mo; Jing Liu; Yuan Xing; Yuanping Wang; Cailin Ge; Yulong Wang (Journal of Plant Growth Regulation, 2021)

Mitogen-activated protein kinase action in plant response to high-temperature stress: a mini review - Shuangrong Mo; Ying Qian; Wenjuan Zhang; Lu Qian; Yan Wang; Ge Cailin; Haidong Ding (Protoplasma, 2021)

A novel alginate localization molding technique for cross-sectional area measurement of human tendon to access biomechanical properties - Xiaojing Ge; Jinju Ding; Minghui Wang; Qi Li; Yongcheng Hu; Dengxing Lun; Lei Zhang; Limin Wang; Wenru Wang; Bin Liu (Cell and Tissue Banking, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

RETRACTED ARTICLE: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

Towards More Snow Days in Summer since 2001 at the Great Wall Station, Antarctic Peninsula: The Role of the Amundsen Sea Low - Minghu Ding; Wei Han; Tong Zhang; Xiaoyuan Yue; Jeremy Fyke; Ge Liu; Cunde Xiao (Advances in Atmospheric Sciences, 2020)

Enhanced Transport of TiO2-Reduced Graphene Oxide Nanocomposites in Saturated Porous Media: the Impact of Loaded TiO2 Shape and Solution Conditions - Jiajing Cao; Xue Bai; Zhengfang Ye; Wei Chen; Haoyu Ge; Yuanyuan Ding; Zulin Hua (Water, Air, & Soil Pollution, 2020)

ACT001 modulates the NF-κB/MnSOD/ROS axis by targeting IKKβ to inhibit glioblastoma cell growth - Qiuying Li; Yu Sun; Bowen Liu; Jiabo Li; Xin Hao; Weizhi Ge; Xuemei Zhang; Shiqi Bao; Jianmiao Gong; Zhenhuan Jiang; Chuanjiang Qiu; Liqing Zhao; et al. (Journal of Molecular Medicine, 2020)

In-depth proteome analysis reveals multiple pathways involved in tomato SlMPK1-mediated high-temperature responses - Haidong Ding; Yuan Wu; Guibo Yuan; Shuangrong Mo; Qi Chen; Xiaoying Xu; Xiaoxia Wu; Cailin Ge (Protoplasma, 2020)

Chemical constituents of Curcuma kwangsiensis and their antimigratory activities in RKO cells - Ju-Tao Wang; Ding Ge; Hai-Fang Qu; Guo-Kai Wang; Gang Wang (Natural Product Research, 2019)

Dysregulated expression of ACTN4 contributes to endothelial cell injury via the activation of the p38-MAPK/p53 apoptosis pathway in preeclampsia - Jianlin Zhao; Wei Peng; Yuxin Ran; Huisheng Ge; Chen Zhang; Hong Zou; Yubin Ding; Hongbo Qi (Journal of Physiology and Biochemistry, 2019)

Dissolved organic carbon dynamics in the East China Sea and the northwest Pacific Ocean - Ling Ding; Tiantian Ge; Xuchen Wang (Ocean Science, 2019)
Oceanic dissolved organic carbon (DOC) represents one of the largest carbon reservoirs on Earth, and its distribution and biogeochemical cycles play important roles in carbon cycling and other biogeochemical processes in the ocean. We report the distribution and concentrations of DOC for water samples collected from the shelf-edge and slope regions in the East China Sea (ECS) and the Kuroshio Extension (KE) in the northwestern North Pacific during two cruises in 2014–2015. The DOC concentrations were 45–88 µM in the ECS and 35–65 µM in the KE. In addition to biological processes that are estimated to account for 7 % and 8 %–20 % in shaping the DOC distribution in the ECS and KE regions, respectively, the DOC distribution is largely controlled by hydrodynamic mixing of different water masses. By comparing the DOC results with dissolved inorganic carbon (DIC) and dissolved inorganic radiocarbon (Δ14C-DIC) measured from the same water samples, we further demonstrate that the intrusion of the Kuroshio Current could dilute the DOC concentrations at stations in the outer shelf and slope regions of the ECS. The concentrations of DOC in the KE were significantly lower in surface waters than in the ECS, and a relatively low and stable DOC level (∼40 µM) was found in deep water (below 1500 m) at all stations. Based on the previously reported DIC and Δ14C-DIC values for the stations, the observed spatial variations of DOC in the upper 700 m among the stations in the KE were mainly influenced by mixing of the two water masses carried by the Kuroshio and Oyashio, the two dominant western boundary currents in the region. The hydrodynamic processes are thus important factors in the distribution and dynamics of DOC in the KE region.

Molecular variation and population structure in endangered Limonium bicolor: genetic diversity of microsatellite markers and amplified fragment length polymorphism analysis - Ge Ding; Daizhen Zhang; Feng Xue; Jian Gao; Kai-Wun Yeh (Journal of Genetics, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Silencing of miR156 confers enhanced resistance to brown planthopper in rice - Yafei Ge; Junyou Han; Guoxin Zhou; Yunmin Xu; Yue Ding; Min Shi; Changkui Guo; Gang Wu (Planta, 2018)

Long-term follow-up of the effects of fecal microbiota transplantation in combination with soluble dietary fiber as a therapeutic regimen in slow transit constipation - Xueying Zhang; Hongliang Tian; Lili Gu; Yongzhan Nie; Chao Ding; Xiaolong Ge; Bo Yang; Jianfeng Gong; Ning Li (Science China Life Sciences, 2018)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Simulation of the osmosis-based drug encapsulation in erythrocytes - Duobiao Ge; Lili Zou; Chengpan Li; Sen Liu; Shibo Li; Sijie Sun; Weiping Ding (European Biophysics Journal, 2018)

Native and non-native halophytes resiliency against sea-level rise and saltwater intrusion - Lian Xue; Xiuzhen Li; Zhongzheng Yan; Qian Zhang; Wenhui Ding; Xing Huang; Bo Tian; Zhenming Ge; Qiuxiao Yin (Hydrobiologia, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Microsatellite records for volume 9, issue 4 - Zhaosheng Cai; Wenxuan Cao; Jie Chen; Jiayin Dai; Ge Ding; Samantha Gray; Jiasheng Hao; Xiayun Jiang; B. B. Li; Yao Li; Z. B. Li; Gang Liu; et al. (Conservation Genetics Resources, 2017)

Influence of Micropatterned Silk Fibroin Films on Human Umbilical Endothelial Cell Behaviors - Danyan Wang; Yan Sun; Xili Ding; Ge Peng; Tongqiang Zou; Haifeng Liu; Yubo Fan (Journal of Medical and Biological Engineering, 2017)

Dispersal modality determines the relative partitioning of beta diversity in spider assemblages on subtropical land‐bridge islands - Lingbing Wu; Xingfeng Si; Raphael K. Didham; Dapeng Ge; Ping Ding (Journal of Biogeography, 2017)
Aim To identify geographical drivers determining the relative partitioning of species replacement and richness difference or nestedness‐resultant components of beta diversity in spider groups with differing dispersal modalities. Location Thousand Island Lake, China. Methods We sampled spider assemblages on 31 land‐bridge islands for two years. Each species was classified into a dispersal group based on ballooning propensity (frequent, occasional or non‐ballooners). Two frameworks were used to separate beta diversity (β cc or β jac ) of each group into either species replacement (β ‐3 ) and richness difference (β rich ) components, or turnover (β jtu ) and nestedness‐resultant (β jne ) components. Mantel and partial Mantel tests were performed to determine correlations between pairwise dissimilarities and difference in island area, difference in distance to mainland and inter‐island distance for each group. Results The multiple‐island dissimilarity of spiders was primarily driven by turnover. Beta diversity (β cc or β jac ) was positively associated with difference in island area in frequent ballooners, and negatively associated with difference in island area in occasional ballooners. Difference in island area had positive effects on β jne for all groups, but negative effects on β ‐3 and β jtu for occasional or non‐ballooners. β rich was positively associated with difference in island area in frequent and non‐ballooners. We did not find any significant isolation effects for these three measures of dissimilarity. Main conclusions The dominant process of extinction resulted in a high contribution of turnover to the multiple‐island dissimilarity of spiders. Specifically, frequent ballooners contributed less turnover to multiple‐island dissimilarity than occasional and non‐ballooners. The most likely explanation for this is that frequent ballooners were potentially able to colonize all islands, whereas occasional and non‐ballooners were constrained by water barriers and were unable to occupy most islands. Contrasting dissimilarities among dispersal groups of spiders demonstrates the importance of beta diversity partitioning, and the mechanistic insight gained on trait‐dependence in community assembly.

Acclimation of Salix triandroides cuttings to incomplete submergence is reduced by low light - Xiaohui Ding; Jianfeng Zou; Youzhi Li; Xin Yao; Dongsheng Zou; Canming Zhang; Nan Yang; Yandong Niu; Hualin Bian; Jiajun Deng; Zixuan Ge (Aquatic Ecology, 2017)

Refractive Errors in Northern China Between the Residents with Drinking Water Containing Excessive Fluorine and Normal Drinking Water - Ge Bin; Haifeng Liu; Chunyuan Zhao; Guangkai Zhou; Xuchen Ding; Na Zhang; Yongfang Xu; Yanhua Qi (Biological Trace Element Research, 2016)

Enhanced Neuroprotection of Acetyl-11-Keto-β-Boswellic Acid (AKBA)-Loaded O-Carboxymethyl Chitosan Nanoparticles Through Antioxidant and Anti-Inflammatory Pathways - Yi Ding; Youbei Qiao; Min Wang; Huinan Zhang; Liang Li; Yikai Zhang; Jie Ge; Ying Song; Yuwen Li; Aidong Wen (Molecular Neurobiology, 2016)

Retrieval of Soil Dispersion Using Hyperspectral Remote Sensing - Jia-ge Chen; Jun Chen; Qin-jun Wang; Yue Zhang; Hai-feng Ding; Zhang Huang (Journal of the Indian Society of Remote Sensing, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Epibrassinolide confers zinc stress tolerance by regulating antioxidant enzyme responses, osmolytes, and hormonal balance in Solanum melongena seedlings - Jie He; Yijun Wang; Haidong Ding; Cailin Ge (Brazilian Journal of Botany, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Application of sequence-related amplified polymorphism to genetic diversity analysis in Limonium sinense - DING GE; ZHANG DAIZHEN (Journal of Genetics, 2015)

Active vibration-attenuation controller design for uncertain structural systems with input time-delay - Yuanchun Ding; Falu Weng; Minkang Tang; Ji Ge (Earthquake Engineering and Engineering Vibration, 2015)

Isolation and characterization of microsatellites in Dendrobium crystallinum and application to germplasm identification - Ge Ding; Daizhen Zhang; Xiaoyu Ding (Conservation Genetics Resources, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Transfer of sclerotinia resistance from wild relative of Brassica oleracea into Brassica napus using a hexaploidy step - Jiaqin Mei; Yao Liu; Dayong Wei; Benjamin Wittkop; Yijuan Ding; Qinfei Li; Jiana Li; Huafang Wan; Zaiyun Li; Xianhong Ge; Martin Frauen; Rod J. Snowdon; et al. (Theoretical and Applied Genetics, 2015)

Common genetic variants on 3q28 contribute to non-small cell lung cancer susceptibility: evidence from 10 case-control studies - Yu-xing Jin; Ge-ning Jiang; Hui Zheng; Liang Duan; Jia-an Ding (Molecular Genetics and Genomics, 2015)

Comparison of spatial sampling strategies for ground sampling and validation of MODIS LAI products - Yanling Ding; Yong Ge; Maogui Hu; Jinfeng Wang; Jianghao Wang; Xingming Zheng; Kai Zhao (International Journal of Remote Sensing, 2014)

Association between CLPTM1L polymorphisms (rs402710 and rs401681) and lung cancer susceptibility: evidence from 27 case–control studies - De-ping Zhao; Chen-lu Yang; Xiao Zhou; Jia-an Ding; Ge-ning Jiang (Molecular Genetics and Genomics, 2014)

Variations in the starting date of the pre-summer rainy season in South China, 1736–2010 - Lingling Ding; Quansheng Ge; Jingyun Zheng; Zhixin Hao (Journal of Geographical Sciences, 2014)

A DEAD-box RNA helicase produces two forms of transcript that differentially respond to cold stress in a cryophyte (Chorispora bungeana) - Yu Yang; Zhenglong Sun; Chenchen Ding; Linna Ge; Likun Sun; Muqun Bai; Yuan Song; Shuyan Chen; Lizhe An (Planta, 2014)

Immunohistochemical localization of Pax6 in the developing tooth germ of mice - Haihua Lei; He Liu; Yun Ding; Lihong Ge (Journal of Molecular Histology, 2014)

Fifteen novel microsatellite markers for rock shell (Thais clavigera) - Hai Li; Jianrong Huang; Shaoxiong Ding; Taiming Ge (Conservation Genetics Resources, 2014)

Nucleolar dominance and different genome behaviors in hybrids and allopolyploids - Xian-Hong Ge; Li Ding; Zai-Yun Li (Plant Cell Reports, 2013)

Coastal evolution of Yancheng, northern Jiangsu, China since the mid-Holocene based on the Landsat MSS imagery - Yanyan Kang; Fei Xia; Xianrong Ding; Changkuan Zhang; Ligang Cheng; Xiaoping Ge; Jennifer Glass (Journal of Geographical Sciences, 2013)

An integrated East China Sea–Changjiang Estuary model system with aim at resolving multi-scale regional–shelf–estuarine dynamics - Jianzhong Ge; Pingxing Ding; Changsheng Chen; Song Hu; Gui Fu; Lunyu Wu (Ocean Dynamics, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Characterization and functional analysis of a novel PGIP gene from Pyrus pyrifolia Nakai cv Huobali - Diqiu Liu; Wenxian Li; Xin He; Yuanming Ding; Chaoyin Chen; Feng Ge (Acta Physiologiae Plantarum, 2013)

Population genetic diversity and divergence of the halobiotic herb Limonium sinense estimated by AFLP and ISSR, and implications for conservation - Ge Ding; Daizhen Zhang; Yanqiu Yu; Lingling Zhao; Beibei Zhang (Plant Systematics and Evolution, 2013)

Development and characterization of microsatellite loci of Oratosquilla oratoria (Crustacea: Squillidae) - Daizhen Zhang; Ge Ding; Baoming Ge; Huabin Zhang; Boping Tang (Conservation Genetics Resources, 2012)

Analysis of the External Pressure on Casings Induced by Salt-Gypsum Creep in Build-up Sections for Horizontal Wells - Weifeng Ge; Mian Chen; Yan Jin; Fuxiang Zhang; Yunhu Lu; Pei Yang; Jihui Ding; Hao Zeng (Rock Mechanics and Rock Engineering, 2011)

Structure and variable numbers of tandem repeats (VNTRs) of the mitochondrial control region in mitten crab Eriocheir (Crustacean: Brachyura) - Daizhen Zhang; Ge Ding; Guangyue Wang; Boping Tang; Hongying Sun (Molecular Biology Reports, 2011)

Impact of long-range transport and under-cloud scavenging on precipitation chemistry in East China - Yuhua Li; Yan Wang; Aijun Ding; Xiaohuan Liu; Jia Guo; Penghui Li; Minghu Sun; Fuling Ge; Wenxing Wang (Environmental Science and Pollution Research, 2011)

Ischemic compression block attenuates mechanical hyperalgesia evoked from latent myofascial trigger points - Yong-Hui Wang; Xin-Li Ding; Yang Zhang; Jing Chen; Hong-You Ge; Lars Arendt-Nielsen; Shou-Wei Yue (Experimental Brain Research, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

On the major proposals for carbon emission reduction and some related issues - ZhongLi Ding; XiaoNan Duan; QuanSheng Ge; ZhiQiang Zhang (Science China Earth Sciences, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Risk to humans of consuming metals in anchovy (Coilia sp.) from the Yangtze River Delta - Fengyan Liu; Jiachun Ge; Xin Hu; Teng Fei; Yuehua Li; Yuan Jiang; Zhiqiang Xu; Shuyan Ding; John P. Giesy; Jianlin Pan (Environmental Geochemistry and Health, 2009)

Isolation and characterization of 10 microsatellite markers in Helice tientsinensis (Brachyura: Varunidae) - Daizhen Zhang; Ge Ding; Huabin Zhang; Boping Tang (Conservation Genetics Resources, 2009)

Genetic variation and conservation of the endangered Chinese endemic herb Dendrobium officinale based on SRAP analysis - Ge Ding; Daizhen Zhang; Xiaoyu Ding; Qi Zhou; Weichao Zhang; Xuexia Li (Plant Systematics and Evolution, 2008)

Production and characterization of intergeneric somatic hybrids between Brassica napus and Orychophragmus violaceus and their backcrossing progenies - Zhi-gang Zhao; Ting-ting Hu; Xian-Hong Ge; Xue-zhu Du; Li Ding; Zai-yun Li (Plant Cell Reports, 2008)

Genetic diversity analysis and conservation of the endangered Chinese endemic herb Dendrobium officinale Kimura et Migo (Orchidaceae) based on AFLP - Xuexia Li; Xiaoyu Ding; Bihai Chu; Qi Zhou; Ge Ding; Sun Gu (Genetica, 2008)

Phylogenetic review of the Chinese species of Acanthacorydalis (Megaloptera, Corydalidae) - Xing Yue Liu; Ding Yang; Si Qin Ge; Xing Ke Yang (Zoologica Scripta, 2005)
The dobsonfly genus Acanthacorydalis Weele is a small genus which only occurs in Asia and comprises eight species. Seven species are restricted to the Oriental realm, while A. orientalis (McLachlan) extends into the Palaearctic realm. There are five species in China, four of which are endemic. In the present paper, the Chinese species are redescribed, illustrated, keyed, and subjected to phylogenetic and biogeographical analyses for the first time. Geographic distributions are updated. The cladistic analysis for the Chinese species was constructed by using Hennig86, based on 17 adult morphological characters. The phylogenetic relationships obtained are ( A. orientalis + A. yunnanensis + A. unimaculata + ( A. fruhstorferi + A. sinensis )). Six areas of endemism are identified based on Acanthacorydalis distributions: north, south‐west, central and south China, north‐eastern India and northern Vietnam.

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Differentiation of apoptotic and necrotic cells in suspension cultures of Taxus cuspidata by the combined use of fluorescent dying and histochemical staining methods - Ying-Jin Yuan; Zhi-Qiang Ge; Jing-Chuan Li; Jin-Chuan Wu; Zong-Ding Hu (Biotechnology Letters, 2002)

Spatial distribution characteristics of urban thermal conditions: application of GIS and remote sensing - Zhou Hong-mei; Zhou Cheng-hu; Ge Wei-qiang; Ding Jin-cai (Journal of Geographical Sciences, 2001)

Allozyme variation in the diploid (A genome) populations ofScilla scilloides (Hyacinthaceae) - Kaiyu Ding; Song Ge; Zhihui Yu; Deyuan Hong (Plant Systematics and Evolution, 1999)